High temperature stability of a commercial terphenyl-based thermal oil. (October 2021) - Mansi, E.; Sau, S.; Balog, I.; Caputo, G.; Corsaro, N.; Tiranti, G.; Filippi, F.; Panza, F.; Ratto, N.; Simonetti, A.; Tizzoni, A.C.; Ciotti, M.; et al.
Abstract: Thermal oils are nowadays largely employed as heat transfer fluids or cooling media in industrial and energy production plants. However, despite their widespread use, very few data are currently available about their chemical stability and possible composition changes in function of the operating temperatures, which are of crucial importance to evaluate the lifetime of these materials in real conditions. In the present work, a commercial terphenyl-based oil was investigated with respect to its thermal stability, performing ageing tests followed by a complete post-characterization analysis. To this purpose, a dedicated experimental set-up was designed and constructed to study the degradation processes, with a qualitatively and quantitatively analysis of the released gases and condensable products, together with a post-ageing characterization of the oil thermo-physical properties. The results show that the main decomposition mechanism involves the loss of hydrogen atoms, followed by partial polymerization processes, which explain the increase in dynamic viscosity and the decrease in volatility observed for the thermally stressed materials. Finally, the decomposition kinetic constants were estimated, obtaining a value of about 100 kJ/mol for the activation energy, which is in good agreement with the data available in the scientific literature.